2018
DOI: 10.1111/jav.01701
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of complete brood failure in blue tits: could extra‐pair mating provide unexplored benefits to females?

Abstract: Behavioural ecologists have for decades investigated the adaptive value of extra‐pair copulation (EPC) for females of socially monogamous species. Despite extensive effort testing for genetic benefits, there now seems to be a consensus that the so‐called ‘good genes’ effects are at most weak. In parallel the search for direct benefits has mostly focused on the period surrounding egg laying, thus neglecting potential correlates of EPC that might be expressed at later stages in the breeding cycle. Here we used B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…Our results thus support the hypothesis that extra‐pair copulations can function as an insurance against the loss of care by a female's social partner. This interpretation is also consistent with recent theoretical and empirical work suggesting that females may benefit from mating with neighbouring males (Eliassen and Jørgensen 2014, Mennerat et al 2018). This potential benefit will usually remain undetected, however, because it is only expressed under specific conditions (when the female lost her mate and the male has no brood of its own).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results thus support the hypothesis that extra‐pair copulations can function as an insurance against the loss of care by a female's social partner. This interpretation is also consistent with recent theoretical and empirical work suggesting that females may benefit from mating with neighbouring males (Eliassen and Jørgensen 2014, Mennerat et al 2018). This potential benefit will usually remain undetected, however, because it is only expressed under specific conditions (when the female lost her mate and the male has no brood of its own).…”
Section: Discussionsupporting
confidence: 92%
“…This is reminiscent of female strategies to secure parental care in species with a more complex social mating system such as the dunnock Prunella modularis (Davies 1985). Although this hypothesis has frequently been postulated, there is little evidence for it (but see Mennerat et al 2018). One reason may be that the benefit is not so easily detected, because visits by other birds than the social pair are not noticed or because the benefit does not always materialize.…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative actions are often more efficient in larger groups ( 1 ). Larger aggregations of breeders may also increase opportunities for male and female neighbors to interact, with extra-pair mating being more prevalent in dense aggregations ( 18 ) and among close neighbors ( 19 , 20 ).…”
mentioning
confidence: 99%
“…Apart from these costs associated with engaging in (extra-pair) mating activities under high risk of predation, however, perceived predation risk may also affect the benefits for females of engaging in extra-pair copulations. For instance, it has been suggested that neighbouring males may help defend the nest against predators if they have copulated with the female at that nest, and that females may therefore benefit more from pursuing extra-pair copulations when predation risk is high (Eliassen & Jørgensen, 2014;Mennerat, Charmantier, Jørgensen, & Eliassen, 2018). It has also been suggested that females may be more likely to engage in extra-pair copulations when adult mortality rate is high, because their partners will be less likely to retaliate by reducing parental care (Arnold & Owens, 2002;Mauck, Marschall, & Parker, 1999).…”
mentioning
confidence: 99%